2017
DOI: 10.1007/s13205-017-1037-6
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of decolorization process in agar production from Gracilaria lemaneiformis and evaluation of antioxidant activities of the extract rich in natural pigments

Abstract: is mainly used as a raw material source for agar industry, and its extract is rich in natural pigments with antioxidant activities. In this study, a solvent reflux extraction method for decolorization of has been developed in agar production. The extraction conditions were optimized as follows: solvent-to-material ratio, 50:1; ethanol concentration, 70%; number of extractions, 3; extraction time, 0.5 h, under which the total antioxidant yield of the extract reached 2.89 ± 0.88 mg/g dried seaweeds. Their IC val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…However, the structures of green tea polysaccharides reported in different literatures have different structures, due to the varieties, origins, and experimental methods. (Yuan et al, 2018). •OH is recognized as the most reactive oxygen free radical, which is highly aggressive and virulent to cells, and is also the main factor of organism peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the structures of green tea polysaccharides reported in different literatures have different structures, due to the varieties, origins, and experimental methods. (Yuan et al, 2018). •OH is recognized as the most reactive oxygen free radical, which is highly aggressive and virulent to cells, and is also the main factor of organism peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors proposed the use of more than one fraction, such as the sequential extraction of R-phycoerythrin and agar from Gracilaria verrucosa [226], Yuan et al [254] proposed an initial extraction of the pigments for decolorization of Gracilaria lemaneiformis before agar production, allowing also to recover the removed fractions as natural antioxidants. Niu et al [261] observed that after water extraction of proteins from Gracilaria lemaneiformis and further purification of R-phycoerythrin the remaining biomass was used for agar extraction.…”
Section: Combined Extractionmentioning
confidence: 99%
“…Algae, has been widely used as a bioactive source metabolites such as proteins, lipids, mineral salts, polyphenols and polysaccharides which are very useful in various industries of food, pharmacy, cosmetics [ 4,5 ]. Red algae is a group of algae that has extraordinary potential, including the pigment content of red algae which has pharmaceutical, nutraceutical and cosmeceutical prospects [ 6,7 ].…”
Section: Introductionmentioning
confidence: 99%